Sales Force Evaluation by Local and Foreign Wholesale Companies in Singapore - Rajah V. Komaran,; Tok Lee Ching, (Asian Academy of Management Journal, 1997)
Sales Force Evaluation by Local and Foreign Wholesale Companies in Singapore(PDF not available)